Effect of Ajwa Date Fruit (Phoenix dactylifera) Methanol Extract on Blood Glucose Levels in Mice with Diabetes Mellitus - Dewanti, Anggita Annisa Wahyu; Susanto, Joni; Apriliawati, Dwi; Yuliawati, Tri Hartini (Universitas Airlangga, 2024)
Highlights: The widespread incidence of DM leads to costly treatments and often results in undesirable side effects. The widespread incidence of DM leads to costly treatments and often results in undesirable side effects. Methanol extract of Ajwa date fruit can effectively lower blood glucose levels in diabetic mice at specific optimal doses. Abstract Introduction: High diabetes mellitus (DM) cases result in costly medical expenses. Ajwa date fruit contains triterpenoids, carbohydrates, and flavonoids believed to lower blood glucose, which requires research validation using methanol extract on streptozotocin (STZ)-induced mice. This study aimed to determine the effect of methanol extract of Ajwa dates with several dose levels, namely 3 g/WB, 5 g/WB, and 7 g/WB, given orally to mice induced by STZ. Methods: This study utilized a randomized pre- and post-test control group design to assess Ajwa date fruit methanol extract effects on blood glucose in Swiss-Webster mice (Mus musculus). The mice were divided into four groups: Group K (6 mice without date extract intervention), P1 (6 mice with 3 g/WB/day oral dose date extract intervention), P2 (7 mice with 5 g/WB/day oral dose date extract intervention), and P3 (7 mice with 7 g/WB/day oral dose date extract intervention) and were induced with 100 mg/WB streptozotocin. Administered daily for three weeks, Ajwa dates fruit extract showed varying impacts. Weekly blood glucose measurements and analysis of variance (ANOVA) in the International Business Machines Corporation (IBM) Statistical Package for the Social Sciences (SPSS) version 27.0 disclosed significant group differences, with a p<0.05 considered statistically significant. Results: Post-test blood glucose measurements in the third week showed a significant difference (p=0.017), with an optimal reduction in P3 (7 mice with 7 g/WB/day oral dose date extract intervention). Conclusion: In the third week, Ajwa dates fruit extract, at an optimal 7 g/WB dose, effectively reduced blood glucose levels via flavonoid hypoglycemic mechanisms.